Proton response and neutron spectrum unfolding by solution-grown trans-stilbene scintillator - Nguyen Duy Quang; H. J. Kim; Sunghwan Kim; Sinchul Kang; Phan Quoc Vuong; Phan Bao Quoc Hieu; Nguyen Kien Cuong; Y. S. Yoon; Uk-Won Nam (Scientific Reports)
Abstract This paper reports the proton response function for solution-grown trans-stilbene scintillator from 1 to 25 MeVee and its application for unfolding neutron spectra of Cf-252 and AmBe sources. Low energy proton response was measured by the Time-of-Flight technique at the Korea Research Institute of Standards and Science. In contrast, high energy response was investigated using a 45 MeV proton beam at the Korea Institute of Radiological & Medical Sciences. The photomultiplier tube nonlinearity effect was studied and corrected for high-energy measurement. Several energy calibration functions were examined to minimize the effects of the light yield nonlinearity of the scintillator, which was observed as nonnegligible in the measurement. A new approach was applied to obtain 1.3 ns full width at half maximum timing resolution in the Time-of-Flight experiment when using a 500 Mega samples per second analog to digital converter. The unfolding was performed using the iterative Bayesian method without any constraints, smoothness, or assumption of prior knowledge of original spectra. For the first time, we achieved one of the best unfolding results for both Cf-252 and AmBe spectra. Results from this study are promising for fast neutron spectroscopy.